Tackling food waste - Mohd Latiff, Nur Hanie; Nazli, Siti Nurshahida (Revon Media Sdn Bhd, 2024)
This article was written to spread the awareness of tackling food waste during the fasting month of Ramadhan. The focused is to teach children the importance of mindful eating and appreciate the value of each meal. This article also integrating the Islamic aspect of practicing the Islamic way of life, moderating in taking meal and steps to reducing food waste.